Operative Management of Hip Fractures Within 24 Hours in the Elderly is Achievable and Associated With Reduced Opiate Use - Sachin Allahabadi MD; Mohammad Roostan MD; Erika Roddy MD; Derek T. Ward MD; Stephanie Rogers MD; Candace Kim MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2022)
Introduction Morbidity and mortality benefits have been associated with prompt surgical treatment of geriatric hip fractures. The purpose of this study was to evaluate the impact of early (≤24 hr) vs delayed (>24 hr) time to operating room (TTOR) on 1) hospital length of stay and 2) total and post-operative opiate use in geriatric hip fractures. Materials and Methods This study was a retrospective review of patients ≥65 years-old at the time of admission for surgery for hip fracture at a Level II academic trauma center. Outcome measures were length of stay (LOS), oral morphine equivalents (OME) throughout hospitalization. Patients were stratified into early and delayed TTOR groups and comparisons were made between groups. Results Between the early (n = 75, 80.6%) and late (n = 18, 19.4%) groups, there were no differences in age, fracture pattern, type of treatment, preoperative opiate use, and perioperative non-oral pain management. The early group trended toward shorter total LOS (108.0 ± 67.2 hours vs 144.8 ± 103.7 hours, P = .066), but not post-operative LOS. Total OME usage was less in the early intervention group (92.5 ± 188.0 vs 230.2 ± 296.7, P = .015), in addition to reduced post-operative OME (81.3 ± 174.9 vs 213.3 ± 271.3, P = .012). There were no differences in evaluated potential delay sources such as primary language, use of surrogate decision makers, or need for advanced imaging. Discussion Surgical treatment of geriatric hip/femur fractures in ≤24 hours from presentation is achievable and may be associated with reduced total inpatient opiate use, although daily use did not differ. Conclusion Establishing institutional TTOR goals as part of an interdisciplinary hip fracture co-management clinical pathway can facilitate prompt care and contribute to recovery and less opiate use in these patients with highly morbid injuries.